2005
DOI: 10.1212/wnl.64.12_suppl_3.s34
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is a chronic neurodegenerative disorder and the most common cause of dementia. It is one of the principal causes of disability and decreased quality of life among older adults. Progress in our clinical knowledge of AD has led to more reliable diagnostic criteria and accuracy, and research efforts are expanding to uncover the earliest manifestations and even the presymptomatic phases of the disease. The diagnosis of AD is primarily one of inclusion and usually can be made using standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(63 citation statements)
references
References 60 publications
0
61
0
2
Order By: Relevance
“…The cause of AD is not yet clear. Pathological studies revealed the existence of neuritic plaques in the brains of AD patients (Desai and Grossberg, 2005;Blennow et al, 2006). The plaques are mainly composed of amyloid-␤ (A␤) peptides that are formed by the sequential cleavage of the amyloid precursor protein (APP).…”
Section: Introductionmentioning
confidence: 99%
“…The cause of AD is not yet clear. Pathological studies revealed the existence of neuritic plaques in the brains of AD patients (Desai and Grossberg, 2005;Blennow et al, 2006). The plaques are mainly composed of amyloid-␤ (A␤) peptides that are formed by the sequential cleavage of the amyloid precursor protein (APP).…”
Section: Introductionmentioning
confidence: 99%
“…They must display high sensitivity and specificity, while ease-of use is also an important factor to be defined as biomarkers. (Desai and Grossberg, 2005; (Alzheimer's, 2015, Hebert et al, 2013, Thies et al, 2013. Humpel, 2011).…”
Section: Current Markers Of Admentioning
confidence: 99%
“…4,5 The prevalence of dementia due to AD increases with age, such that AD accounts for 5% of dementia cases in the age group of 65-74 years and 50% in the age group over 85 years. 6 AD is responsible for reduction of life expectancy by 50% from the time of diagnosis in elderly patients. 7 AD is characterized by destruction of the functional activity of neurons in the cerebral cortex, amygdale, frontal base, limbic system and hippocampus, and also by cortical atrophy, thereby causing impairment of cholinergic synapses in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%